Consumption Expenditure on Processed Meat and Its Correlates: An Ethnic Comparison. - Cheah, Yong Kang; Appannah, Geeta; Abdul Adzis, Azira (Nutrition & Cancer, 2023)
Background: The objective of the present study is to investigate the influences of sociodemographic and household factors on consumption expenditure on processed meat among households in Malaysia. Methods: Data were extracted from the Malaysian Household Expenditure Survey (HES) 2016. Lognormal hurdle models were utilized to assess the likelihood of consuming processed meat and the amount consumed. The independent variables consisted of household heads' age, educational level, gender, marital status, employment status, ethnicity, as well as household income, household region and household locality. Results: Bumiputera households with younger heads were more likely to consume processed meat and spent more than households with older heads. Chinese and Indian households in a higher income group had a higher likelihood of consuming and spending on processed meat than those in a lower income group. The probability of consuming processed meat and the amount consumed were positively associated with being from East Malaysia and urban areas. Conclusions: There are distinguished roles of sociodemographic and household factors across ethnic groups in consumption expenditure on processed meat. Policy makers should take account of age, income, education, household region and household locality factors when formulating intervention measures.